Digital Craft: A Contemporary Bauhaus Model from Design through Build. (EAAE Annual Conference Proceedings, 2023)
Emerging technologies and digital fabrication have revolutionized architectural education and practice, transforming the methods and tools of making in the design process that progress an idea from creative artistic vision into the fabricated built environment. Contemporary architectural education, pedagogically rooted in Bauhaus principles, must therefore utilize the advantages of these modes of making, fundamentally aligning teaching methodologies to the technologies that forge this process.